Population-Based Study Found Low Risk of Misdiagnosing Long QT Syndrome as Breath-Holding Spells in Swedish Children - Schmidt, Sanna Hellström ; 0009-0001-3424-0016; Jeremiasen, Ida ; 0000-0002-5947-4759; Eklund, Erik A.; Pronk, Kees-Jan (Acta Paediatrica, International Journal of Paediatrics, 2026)
Aim: An electrocardiogram is commonly recommended in breath-holding spell management, mainly to rule out long QT syndrome. This retrospective study investigated the risk of long QT syndrome being misdiagnosed as breath-holding spells in a paediatric population in southern Sweden. Methods: Data on patient characteristics and diagnostic findings were reviewed for patients aged < 10 years who were diagnosed with long QT syndrome between 2004 and 2018. Results: Sixteen children were diagnosed with long QT syndrome; 10 were diagnosed through genetic screening, 4 following perinatal cardiac symptoms, and 2 due to episodes of syncope or seizures later diagnosed as epilepsy and breath-holding spells. Three patients were > 24 months old at suspicion of long QT syndrome, and 10 were < 3 months old. No patient exhibited symptoms directly attributable to long QT syndrome, and no diagnosis of long QT syndrome was delayed due to suspicion of or misdiagnosis as breath-holding spells. Conclusions: The number of symptomatic long QT syndrome cases overlapping with the presentation of breath-holding spells is likely small. The findings of this study suggest that children < 3 months old with suspected breath-holding spells should undergo an electrocardiogram.
Publisher Copyright: © 2026 The Author(s). Acta Paediatrica published by John Wiley & Sons Ltd on behalf of Foundation Acta Paediatrica.
Keywords: breath-holding spells; electrocardiography; long QT syndrome; misdiagnosis